Pengembangan Aplikasi Identifikasi Kesalahan Baca Alquran Menggunakan Speech Recognizer Dengan Metode Levenstein Distance Pada Platform Android - Galang Putratama; Agi Putra Kharisma; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Alquran is Muslims holy book which have to be read by paying attention to its letters pronunciation. Because even a little mistake in pronunciation resulting in damage to the meaning of Alquran itself. The process of learning to read the Koran requires a guide to correct mistakes that might occur. However, due the limited of time, then there is also limited opportunity for someone to practice reading Koran with a guide. One solution that the author offers is through the media based on Android application to detect errors in reading the verses of Koran. In the development of the application, the Waterfall method was used which began with interviews with a mosque imam and 2 students. Then the application is designed with the Object Oriented Design method and implemented with the Object Oriented Programming method. The result of its implementation is that the application utilizes Speech Recognizer to translate user readings into Arabic text. While Levenstein Distance algoritm and Diff Match Patch Library handle the error detections in user's pronunciation. At the accuracy testing stage it was found that this application successfully completed 3 of the 4 test cases performed. While at the usability testing stage with the System Usability Scale method this application gets a score of 76 with a level of satisfaction B + or above average. The application must be further developed because the level of accuracy obtained is still too low.